APPORT DES SIG POUR L‟ESTIMATION DES NIVEAUX D‟EAUX EN PLAINE INONDÉE – GHARB, MAROC - Fofana Oumar; Bouabdli Abdelhak; Baghdad Bouamar; Sossey-Alaoui Faiçal (European Scientific Journal, ESJ, 2014)
The present study focuses on the mapping of flood hazards in theGharb (Morocco), all through the use of GIS. Satellite images of river‘sflood are rich in information which are mostly only partially exploited. Inaddition to traditional approaches that aim to map flooded tracts, it isimportant to develop the satellite images by quantifying the spatialdistribution of water levels. We have determined the flood hazard bymeasuring the water level by coupling the map after extensive floodingsatellite image with topographic data. The water‘s levels estimation comingfrom the cross are obtained in an intervals forms [Min, Max], 9 classes ofwater depth were identified: less than 25 cm, 25-50 cm, 50-75 cm, 75-100cm, 100-125 cm, 125-150 cm, 150-175 cm, 175-200 cm and then more than200 cm.